Pengaruh Profitabilitas, CIR, Size, dan Leverage pada Manajemen Pajak Perusahaan Manufaktur di BEI 2012-2015 - Sinaga, Ricco Ronaldo; Sukartha, I Made (E-Jurnal Akuntansi, 2018)
Tax management is the management of tax obligations by employing strategies to minimize the amount of tax burden. Variables that are expected to affect tax management include profitability, capital intensity ratio, size, and leverage. The purpose of this study is to determine the effect of profitability, capital Intensity Ratio, Size and Leverage on tax management. This research is conducted in Indonesia Stock Exchange in Manufacturing Sector period 2012-2015, with nonprobability sampling, especially purposive sampling. Data collection was done through non participant observation. The analysis technique used is multiple liniear regression. From the results of data analysis proves that there is a positive effect of profitability, capital intensity ratio, size and leverage of companies in tax management in manufacturing companies listed on the Indonesia Stock Exchange period 2012-2015. These effects occur simultaneously and partially. Keywords : Profitability, capital intensity ratio, size, leverage, tax management